An Analysis Of Aircraft Exterior Lightin Indicator Control System Based On Arduino Atmega 256 - Yosepa Anggreani Sinaga; Solly Aryza; Amani Darma Tarigan (Sean Institute, 2024)
With the development of technology, there are some basic things that must be known and learned about airplanes, one of which is the exterior lighting system where the functions and uses vary. Exterior lighting plays an important role in airplanes on land and in the air and is a basic thing in knowing this exterior lighting system such as the layout, color and function of the lighting. For this reason, research and the creation of exterior lighting indicators on airplanes based on Arduino Atmega 2560 were conducted. In the research and creation of this tool, the main input from this tool is an adapter that produces a voltage of 5 V. Then there are 8 toggle switches that function as switches for each LED. In general, when the toggle switch is in the ON condition, the current and voltage have been sent to the system as a whole. Then the Arduino Atmega 2560 will process the inputted data. Furthermore, the Arduino Atmega 2560 sends the processed data to each LED so that the LED can light up according to its function and use. For the information generated such as each LED is on or not can be seen on the LCD. The results of functional testing show that the design is able to carry out the function of each LED. The design has a flash rate of beacon light of 45 times per minute and a flash rate of strobe light of 60 times per minute. Taxi light, Logo light, Landing light, Navigation light, Takeoff light, Runway light and Wing light do not have a flash rate or are steady. There is a time difference or delay between the wings strobe light and the tail strobe light of 1 second. The indicator can display information if there is damage to the LED.